2010
DOI: 10.1089/jir.2009.0018
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell–Mediated Cytokine Response Among HIV-Positive South Indians With Pulmonary Tuberculosis

Abstract: Natural killer (NK) cells control Mycobacterium tuberculosis infection mainly through secreted cytokines. Cytokine dysregulation among HIV may cause rapid disease progression. Our objective was to examine whether impaired production of innate cytokines are responsible for cytokine dysregulation during HIV infection. The study included 30 subjects each of normal healthy subjects (NHS), pulmonary tuberculosis patients (TB), HIV-infected individuals (HIV), and HIV-TB co-infected patients (HIV-TB). Intracellular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…These results reflect the interplay between pro-inflammatory and regulatory cytokines in TB/HIV patients and could indicate the establishment of regulatory mechanisms to control the exacerbated inflammatory response by the innate immune system in TB/HIV patients. Similar to our results, lower frequency of NK intracellular pro-inflammatory cytokines, IFN-γ and TNF-, were observed in TB/HIV patients from India compared to healthy controls (80).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results reflect the interplay between pro-inflammatory and regulatory cytokines in TB/HIV patients and could indicate the establishment of regulatory mechanisms to control the exacerbated inflammatory response by the innate immune system in TB/HIV patients. Similar to our results, lower frequency of NK intracellular pro-inflammatory cytokines, IFN-γ and TNF-, were observed in TB/HIV patients from India compared to healthy controls (80).…”
Section: Discussionsupporting
confidence: 91%
“…Although NK cells regulate immune responses through cytokines secretion (79), there are few reports describing the NK regulatory cytokine secretion patterns in TB/HIV patients (80). In our study, TB/HIV patients showed a lower frequency of intracellular IFN-γ-producing NK cells compared to the HC group, as well as of TNF- compared to HIV, TB, and HC groups.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, NK cells from individuals with HIV-1 and pulmonary tuberculosis failed to produce IFN-γ when stimulated in vitro with live M. tuberculosis . 81 Thus, understanding the mechanisms underlying HIV-1-associated NK cell dysfunction could aid in the development of therapies designed to enhance or restore innate immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…IL-2–activated NK cells are known to increase the lytic activity compared with circulating NK cells and are able to lyse otherwise NK cell–resistant targets [10]. The potential effects of IL-15+ IL-12 on the enhancement of NK activity in HIV positive individuals have been demonstrated by us [8], [11], [12]. Hence, the present study assessed the effect of IL-15+ IL-12 on the expression of NK surface receptors in HIV positive individuals with and without TB co-infection.…”
Section: Introductionmentioning
confidence: 99%